Acute effects of air pollution on pediatric asthma exacerbation: Evidence of association and effect modification - Samoli, E.; Nastos, P. T.; Paliatsos, A. G.; Katsouyanni, K.; Priftis, K. N. (Environmental Research, 2011)
We investigated the short-term effects of particulate matter with aerodynamic diameter <10γg/m3 (PM10), sulfur dioxide (SO2), nitrogen dioxide (NO2) and ozone (O3) on pediatric asthma emergency admissions in Athens, Greece over the period 2001-2004. We explored effect modification patterns by season, sex, age and by the presence of desert dust transported mainly from the Sahara area.We used daily time-series data provided by the children's hospitals and the fixed monitoring stations. The associations were investigated using Poisson regression models controlling for seasonality, weather, influenza episodes, day of the week and holiday effects.A 10γg/m3 increase in PM10 was associated with a 2.54% increase (95% confidence interval (CI): 0.06%, 5.08%) in the number of pediatric asthma hospital admissions, while the same increase in SO2 was associated with a 5.98% (95% CI: 0.88%, 11.33%) increase. O3 was associated with a statistically significant increase in asthma admissions among older children in the summer. Our findings provide limited evidence of an association between NO2 exposure and asthma exacerbation. Statistically significant PM10 effects were higher during winter and during desert dust days, while SO2 effects occurred mainly during spring.Our study confirms previously reported PM10 effects on emergency hospital admissions for pediatric asthma and further provides evidence of stronger effects during desert dust days. We additionally report severe effects of SO2, even at today's low concentration levels. © 2011 Elsevier Inc.
Keywords: Adolescent; aerodynamics; Air Pollutants; Air pollution; article; asthma; Athena; atmospheric pollution; Child; child health; Child, Preschool; Children; desert; Desert dust; desert soil; diameter; disease exacerbation; dust; Female; Greece; health monitoring; hospital admission; Hospitalization; human; Humans; Infant; influenza; Male; Newborn; nitrogen dioxide; Oregon; Ozone; Particulate matter; preschool child; priority journal; Regression Analysis; Sahara; seasonal variation; Seasons; spring; Sulfur dioxide; time series; Time-series; United States; Weather